Land Suitability Assessment of Green Infrastructure Development: A Case Study of Pendik District (Turkey) - Ustaoglu, Eda; Aydınoglu, Arif Cagdas (TeMA - Journal of Land Use, Mobility and Environment, 2019)
Urban green space, an integral part of urban ecosystems, provides important environmental and social services that mitigate environmental problems caused by rapid urbanisation and urban sprawl. Urban planning and policy aim at optimising the benefits obtained from urban green spaces. The analytic hierarch process (AHP) is a commonly used technique for suitability assessment of land uses. The traditional AHP method is criticised for its subjectivity and uncertainty. Considering this, Fuzzy-AHP has been introduced as an advanced methodology in dealing with the uncertainty in the decision making process. In this study, we compared the two methods of AHP and fuzzy-AHP integrated with geographic information systems (GIS) for the suitability assessment of Pendik district, Istanbul regarding green space development. First, criteria and sub-criteria were determined and the corresponding weights were assigned based on literature and experts’ knowledge. This is followed by preparation of spatial maps integrated with the corresponding weights and development of final suitability maps in both methods of AHP and fuzzy-AHP. Our results show that high suitability areas are mainly distributed in the southern part of Pendik district around the existing urban green infrastructure. In both maps obtained from AHP and fuzzy-AHP, more than 30 percent of the study area has the potential for green space development.